Genetics of hereditary spastic paraplegia - Tucci, Arianna (Henry Stewart Talks, 2014)
Definition and overview of Hereditary spastic paraplegia (HSP), The motor system in HSP, HSP pathophysiology HSP, Heterogeneity of HSP, Neuropathology in HSP, Clinical features & classification, Diagnosis and treatment, Genetics: general features, Timeline of HSP genetic discoveries, Autosomal dominant and recessive inheritance & genes, X-linked genes, Pathogenic mechanisms